AB0799 Blood flow restriction: the future of musculoskeletal rehabilitation?. (23rd January 2014) - Farrow, L.; Bukhari, M.
Abstract : Background: Musculoskeletal disease has a significant burden on the health of the population, with loss of strength and function a common consequence. Rehabilitation using isometric resistance training is a widely established method of attempting to restore functional ability and strength. This training has typically been considered most effective using high loads of a minimum 60-70% of an individual's 1 repetition maximum. Such mechanical stress does however produce a significant injury risk, particularly in the elderly or infirm population. One potentially safe and effective alternative is low load resistance training with blood flow restriction (LI-BFRT) [also known as Kaatsu training]. This is usually performed by creating an occlusion pressure proximal to the target muscle, restricting the arterial and venous flow around the muscle leading to an enhanced training effect. Objectives: The purpose of this review is to examine the physiology behind proposed strength gains with LI-BFRT, the current evidence for LI-BFRT in rehabilitation, and the risk-benefit of training regimes. Methods: Searches were performed through EBSCO SPORTDiscus & Ovid MEDLINE using a combination of terms including "blood flow restriction", "Kaatsu training", "low load resistance training" and "ischaemic exercise". Potentially relevant articles were included based on abstract analysis and through exploration of bibliographical citations. Review of full article text was then used to identify those papers adequate for inclusion. Results: 29 studies were used in the analysis after full text review, which assessed a total of 319 participants (not including the structured reviews or the large longitudinal cohort study regarding safety). 8 Papers concerned physiology research with 2 cohort studies (22 participants), 2 controlled trials (37 participants) and 3 systematic reviews. 16 papers concerned strength & rehabilitation evidence; there were 9 randomised controlled trials (187 participants), 4 controlled trials (40 participants), 1 case report and 1 systematic review. All of these studies showed a positive effect for LI-BFRT. 5 articles related to LI-BFRT risk; there were 1 randomised controlled trial (16 participants), 1 controlled trial (9 participants), 1 large observational study (12, 462 participants), 1 case report and 1 systematic review. 4 out of the 5 articles had evidence suggesting LI-BFRT was safe. Conclusions: Although differences in study design and quality made comparison difficult there was sufficient evidence to suggest that LI-BFRT is safe, and as effective as traditional high intensity training in the rehabilitation setting. The underlying physiological processes are still unclear but both local muscle growth factors and increased motor unit recruitment appear to be involved in the hypertrophic response. LI-BFRT therefore appears to provide a low force method of training suitable for individuals where high load resistance exercise would be potentially harmful, such as during rehabilitation from injury or those with a high injury risk due to chronic disease. Further research is still needed to identify the exact physiological events underpinning the training effect, the optimum value for technical parameters involved and the potential for use in a post-surgical setting. Disclosure of Interest: None Declared